Automatic Exchange of Information on Indonesia Jurisdiction in order to Control Business Opportunities - Adrian Adhitana Tedja; Vincent Arta Wijaya; Jevelyn Lidyawati (Notaire, 2019)
The Automatic Exchange of Information (AEOI) is a product of  common reporting standard as a result of Indonesia's ratification of the Convention on Mutual Administrative Assistance in Tax Matters. The convention purpose is to  prevent transnational tax evasion and money laudry, with the existence of an automatic exchange of information system through out members of the convention can enact and enforce its laws. The main problems concerning an autamated system is the jurisdiction regarding the enacting state, as well as bank secrecy laws in ratifying countries. With banks are compromised to reveal tax payers information to the state, many tax payers will eventually lose interest in one state and start seeking tax havens, which will impact the economy and business sectors as well as trade policies between states. The purpose of this research is to find out what law governs AEOI in Indonesia and its impact on transnational jurisdiction between ratifying and non-ratifying states. This research is a juridical-emphirical research which uses statute approach, conceptual approach and comparative approach. The research compares Indonesia laws including banking law as well as statistics of Indonesian economic growth since the enactment of tax amnesty as a reaction towards AEOI.